2022
DOI: 10.3390/su14148371
|View full text |Cite
|
Sign up to set email alerts
|

Digitalisation as the Indicator of the Evidence of Sustainability in the European Union

Abstract: Digitalisation provides access to an integrated network of information that can benefit society and businesses. However, the evidence of sustainability in business is less researched. In our paper, by building up the research approach, we address the relevant gap by investigating how sustainable development goals represent the interrelationship between digitalisation and sustainability. Such research is particularly important because understandings of digitalisation and sustainability determine how different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 102 publications
0
10
0
1
Order By: Relevance
“…By employing factor analysis, the hypothesis was validated that two main factors, macroeconomic stability and research and development and digitalization 2 , are significant for strengthening competitiveness in European countries [18]. Digitalization (captured in a simplified manner, using information and communication technology indicators) was considered to provide a view of sustainable competitiveness for a more extensive set of 127 countries [19] and to enhance sustainability by verifying the relationship with five of the sustainable development goals of the United Nations, in the case of European Union countries [20].…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…By employing factor analysis, the hypothesis was validated that two main factors, macroeconomic stability and research and development and digitalization 2 , are significant for strengthening competitiveness in European countries [18]. Digitalization (captured in a simplified manner, using information and communication technology indicators) was considered to provide a view of sustainable competitiveness for a more extensive set of 127 countries [19] and to enhance sustainability by verifying the relationship with five of the sustainable development goals of the United Nations, in the case of European Union countries [20].…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Dijital bankacılık, geleneksel bankacılığa göre daha az enerji tüketmekte ve daha az karbon salınımına yol açmaktadır. Finansal hizmetlerin verildiği alanların fiziksel varlığı azalırken, dijital platformlar ve çevrimiçi işlemler enerji tasarrufu sağlayarak, çevre üzerinde olumlu bir etki oluşturmakta ve karbon ayak izinin azalmasına katkı sağlamaktadır (Burinskienė ve Seržantė, 2022).…”
Section: Dijital Finansal Hizmetlerin çEvresel Etkileriunclassified
“…The authors proved that it is an important indicator for measuring the capabilities of digitalization to determine achieving sustainable development goals. In the same context, several authors [16,[19][20][21] found that digitalization is very important and has a positive impact on sustainable development goals.…”
Section: Introductionmentioning
confidence: 96%
“…Some researchers have proved that digitalization is an essential factor in achieving sustainable development goals [13,14]. Other studies demonstrate that digitalization is a complementary factor to other goals, especially industry, innovation, and infrastructure, noted as SDG9 [15][16][17]. Based on qualitative and quantitative analyses, [18] examined the relationship between SDGs and the composite index to measure digitalization.…”
Section: Introductionmentioning
confidence: 99%